Preparation method and application of double-coated silicon alloy composite material

Magnetron sputtering of phosphorus and amorphous carbon layers on silicon alloy materials addresses conductivity and expansion issues, enhancing performance and efficiency for lithium-ion battery electrodes.

CN116053430BActive Publication Date: 2024-12-20SHINGHWA ADVANCED MATERIAL TECH (MEISHAN) CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211641820.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-20
Publication Date
2024-12-20
Estimated Expiration
2042-12-20

AI Technical Summary

Technical Problem

Existing silicon-based negative electrode materials for lithium-ion batteries face issues with poor electronic conductivity, particle agglomeration, large material expansion, and inefficient production processes, which include high-temperature sintering and mechanical grinding, leading to low power performance and complex preparation cycles.

Method used

A method involving magnetron sputtering to deposit a phosphorus film and amorphous carbon layers on a catalyst-doped silicon alloy, enhancing specific capacity, conductivity, and restraining expansion, with a controllable and efficient process suitable for industrial application.

Benefits of technology

The method improves the specific capacity, conductivity, and power performance of silicon alloy composite materials, reducing expansion during charging and discharging, and offers high preparation efficiency and uniformity, suitable for industrial-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116053430B_ABST
    Figure CN116053430B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a double-coated silicon alloy composite material, comprising the following steps: S1), placing a porous silicon alloy in a 1-10wt% catalyst solution, reacting at a temperature of 60-100°C for at least 1 hour, filtering and drying to obtain a catalyst-doped silicon alloy material; S2), using the catalyst-doped silicon alloy material obtained in step S1) as a matrix, a phosphite compound as a target emission source A1, and a carbon source as a target emission source A2, to prepare an amorphous carbon and phosphorus double-layer coated silicon alloy composite material by a magnetron sputtering method; the invention relies on the high specific capacity of phosphorus itself to improve the specific capacity and combines with amorphous carbon deposited by subsequent magnetron sputtering method to simultaneously improve the electronic conductivity and power performance of the material, and further restrain the expansion of silicon during charging and discharging; and compared with the conventional gas phase method, the application has the advantages of high preparation efficiency and controllable process, and is suitable for industrial-scale promotion and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery material preparation, and specifically relates to a preparation method and application of a double-coated silicon alloy composite material. Background Art

[0002] Among the negative electrode materials of lithium-ion batteries, single silicon has the highest theoretical specific capacity (the theoretical specific capacity of silicon negative electrode materials can reach 4200mAh / g). Since silicon negative electrode materials have a low lithium insertion potential, relative to the lithium electrode potential, its lithium storage potential is less than 0.5V, and silicon materials have abundant reserves, silicon is considered to be the most ideal negative electrode material for the next generation of lithium-ion batteries.

[0003] However, the electronic conductivity of silicon materials is poor and their particles are small. They are easy to agglomerate during the preparation process, causing large local expansion of the material. At the same time, the preparation generally requires two high-temperature preparation processes: preparing silicon oxide compounds under vacuum conditions at 1500-2000℃, and then carbonizing and depositing amorphous carbon at 700-1000℃. Not only does it need to be operated under high temperature conditions, but the preparation cycle is long, resulting in its production efficiency being restricted to a large extent. In addition, in order to improve power performance, it is usually necessary to add metal compounds to the process of preparing silicon to prepare silicon alloys. Specifically, it needs to be prepared by mechanical grinding or high-temperature sintering and mixing. There are also problems such as long preparation cycle and poor uniformity, which leads to the problem that the power increase of silicon materials is not large, the expansion reduction is limited, and the process is complicated.

[0004] Therefore, the applicant hopes to seek technical solutions to improve the above technical problems. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a preparation method and application of a double-coated silicon alloy composite material, by depositing a phosphorus film on the substrate surface of a catalyst-doped silicon alloy material by magnetron sputtering, relying on the high specific capacity of phosphorus itself to improve the specific capacity of the composite material and compounding it with amorphous carbon deposited by subsequent magnetron sputtering, thereby simultaneously improving the electronic conductivity and power performance of the material, and further restraining the expansion of silicon during charging and discharging; and the present application has the advantages of high preparation efficiency and controllable process, and is suitable for industrial-scale promotion and application.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A method for preparing a double-coated silicon alloy composite material comprises the following steps:

[0008] S1), placing the porous silicon alloy in a 1-10wt% catalyst solution, reacting at a temperature of 60-100°C for at least 1 hour, filtering and drying to obtain a catalyst-doped silicon alloy material;

[0009] S2), using the catalyst-doped silicon alloy material obtained in step S1) as a matrix, a phosphite compound as a target emission source A1, and a carbon source as a target emission source A2, amorphous carbon and phosphorus double-layer coated silicon alloy composite material is prepared by magnetron sputtering.

[0010] Preferably, the step S2) includes the following steps:

[0011] S21), turning on the target emission source A1, and depositing a phosphorus film on the surface of the catalyst-doped silicon alloy material by magnetron sputtering, wherein the thickness of the phosphorus film is 50-500 nm, to obtain a phosphorus-doped silicon alloy composite material;

[0012] S22), stop the target emission source A1, start the target emission source A2, and deposit amorphous carbon on the surface of the phosphorus-doped silicon alloy composite material to obtain the amorphous carbon and phosphorus double-layer coated silicon alloy composite material.

[0013] Preferably, the method for preparing the porous silicon alloy in step S1) comprises: corroding the Si / Ag / Al alloy in a 10-40wt% acid solution for at least 15 hours, filtering, washing and drying to obtain the porous silicon alloy.

[0014] Preferably, the Si / Ag / Al alloy includes 60-90 wt % of Si atoms, 5-15 wt % of Ag atoms, and 5-15 wt % of Al atoms.

[0015] Preferably, the catalyst in step S1 is selected from one of ferric chloride, cobalt chloride, nickel chloride, cobalt sulfate, cobalt sulfate, and nickel sulfate, or a mixture of any of them.

[0016] Preferably, in the magnetron sputtering method of step S2), the sputtering atmosphere used is argon, and / or the sputtering gas pressure is 1-10 Pa, and / or the sputtering current is 100-200 mA, and / or the sputtering voltage is 100-300 V, and / or the sputtering temperature is 150-200° C., and / or the sputtering time is 5-20 minutes.

[0017] Preferably, in step S2), the phosphate compound is selected from one of ammonium phosphate, diammonium hydrogen phosphate, silicon phosphate, calcium phosphate, magnesium phosphate, basic copper phosphate, diammonium phosphate, nickel phosphate, or a mixture of any of them.

[0018] Preferably, in the step S2), the carbon source is selected from one of asphalt, artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon, or a mixture of any of them.

[0019] Preferably, a double-clad silicon alloy composite material is prepared by the preparation method of the double-clad silicon alloy composite material as described above.

[0020] Preferably, an application of the double-coated silicon alloy composite material as described above is to use the double-coated silicon alloy composite material as an active material raw material for preparing battery pole pieces.

[0021] The present application obtains a catalyst-doped silicon alloy material by doping a catalyst in the pores of a porous silicon alloy, and uses the catalyst-doped silicon alloy material as a matrix, and deposits a phosphorus film on the matrix surface of the catalyst-doped silicon alloy material by magnetron sputtering, thereby relying on the high specific capacity of phosphorus itself (the theoretical capacity can reach 2595 mAh / g) to improve the specific capacity of the composite material, and to combine it with amorphous carbon deposited by subsequent magnetron sputtering to simultaneously improve the electronic conductivity and power performance of the material, and further restrain the expansion of silicon during the charge and discharge process; and compared with the conventional gas phase method, the magnetron sputtering method adopted in the present application has the advantages of high preparation efficiency and controllable process, and is suitable for industrial-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of the double-coated silicon alloy composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] This embodiment provides a method for preparing a double-coated silicon alloy composite material, comprising the following steps:

[0024] S1), placing the porous silicon alloy in a 1-10wt% catalyst solution, reacting at a temperature of 60-100°C for at least 1 hour, more preferably 1-6 hours, and further preferably 2.5-5 hours, filtering and drying (preferably vacuum drying) to obtain a catalyst-doped silicon alloy material;

[0025] Preferably, the preparation method of the porous silicon alloy in step S1) includes: placing the Si / Ag / Al alloy in a 10-40wt% acid solution (preferably a sulfuric acid solution, which has a more uniform and effective corrosion effect on the porous silicon alloy) and corroding it (preferably at room temperature, more preferably at a temperature of 20-40°C) for at least 15 hours, preferably 20-30 hours, and filtering, washing and drying (preferably vacuum drying) to obtain a porous silicon alloy; preferably, in this embodiment, the Si / Ag / Al alloy includes 60-90wt% Si atoms, 5-15wt% Ag atoms, and 5-15wt% Al atoms, and the raw materials can be configured by yourself and then sintered to obtain a Si / Ag / Al alloy sheet, or it can be purchased directly from the market or customized from an alloy raw material manufacturer; it should also be noted that other Si metal alloys with similar effects can also be selected, and this embodiment does not impose the sole limitation on them.

[0026] Preferably, in this embodiment, the catalyst in step S1 is selected from one of ferric chloride, cobalt chloride, nickel chloride, cobalt sulfate, cobalt sulfate, nickel sulfate, or a mixture of any of them; this embodiment, by doping the catalyst in the pores in the porous silicon alloy, can facilitate the deposition of phosphorus on the surface of the porous silicon and enhance the bonding force between the materials.

[0027] S2), using the catalyst-doped silicon alloy material obtained in step S1) as a matrix, using a phosphite compound as a target emission source A1, and using a carbon source as a target emission source A2, amorphous carbon and phosphorus double-layer coated silicon alloy composite material is prepared by magnetron sputtering; preferably, this step S2) specifically includes the following operating steps:

[0028] S21), turning on the target emission source A1, and depositing a phosphorus film on the surface of the catalyst-doped silicon alloy material by magnetron sputtering, wherein the thickness of the phosphorus film is 50-500 nm, to obtain a phosphorus-doped silicon alloy composite material;

[0029] S22), stop the target emission source A1, start the target emission source A2, and deposit amorphous carbon on the surface of the phosphorus-doped silicon alloy composite material to obtain an amorphous carbon and phosphorus double-layer coated silicon alloy composite material.

[0030] Preferably, in order to ensure the coating deposition effect of the phosphorus film and amorphous carbon on the surface of the material matrix, in the magnetron sputtering method in this step S2), the sputtering atmosphere used is argon, and / or the sputtering gas pressure is 1-10Pa, and / or the sputtering current is 100-200mA, and / or the sputtering voltage is 100-300V, and / or the sputtering temperature is 150-200°C, and / or the sputtering time is 5-20min (specifically refers to the independent start-up sputtering time of the target emission source A1 and the target emission source A2).

[0031] Preferably, in this step S2), the phosphate compound is selected from one of ammonium phosphate, diammonium hydrogen phosphate, silicon phosphate, calcium phosphate, magnesium phosphate, basic copper phosphate, diammonium phosphate, and nickel phosphate, or a mixture of any of them. Of course, other phosphate compounds with similar effects can also be used, and this embodiment does not impose the sole restriction on them; the carbon source is selected from one of asphalt, artificial graphite, natural graphite, mesophase carbon microbeads, hard carbon, and soft carbon, or a mixture of any of them. Of course, other carbon sources with similar effects can also be used, and this embodiment does not impose the sole restriction on them.

[0032] It should be specially noted that the Si / Ag / Al alloy sheet raw materials, catalysts, phosphite compounds and carbon sources involved in the implementation of this application can be directly purchased from the market. The raw materials are abundant and easy to obtain, so this application does not make a special explanation on them.

[0033] It should also be noted that the present application cites various preferred range parameters in the above preparation method after a large number of experimental tests. Those skilled in the art can choose within these preferred parameter ranges (including their endpoint values ​​and intermediate values) according to actual conditions. In order to save space in the specification, this embodiment will not be expanded one by one.

[0034] Preferably, the present embodiment further proposes a double-clad silicon alloy composite material, which is prepared by the preparation method of the double-clad silicon alloy composite material as described above in the present embodiment.

[0035] Preferably, according to an application of the double-coated silicon alloy composite material as described above, the double-coated silicon alloy composite material is used as an active material raw material for preparing battery pole pieces; specifically, it can be used as a battery negative electrode sheet, which can be selected according to actual requirements; in the specific implementation, the process for preparing the battery negative electrode sheet can adopt any known process, which does not belong to the innovative content of the present application, and the present application does not impose any restrictions on it; it should also be noted that when the present application is implemented, the battery can be a button battery, a soft-pack battery or other well-known batteries, and technical personnel in this field can apply it according to actual needs, and the present application does not impose any special restrictions on this.

[0036] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0037] Based on the above-described implementation scheme, the present application further proposes the following specific embodiments:

[0038] Embodiment 1:

[0039] Prepare porous silicon alloy, the preparation process is as follows:

[0040] 100g of Si / Ag / Al alloy sheet (weight ratio of 80wt% Si, 10wt% Ag, 10wt% Al, sintered at high temperature) was placed in 1000ml of 30wt% sulfuric acid solution, corroded at room temperature of 30°C for 24 hours, filtered, washed with deionized water 10 times, and then vacuum dried at 80°C for 24 hours to obtain a porous silicon alloy material.

[0041] Step S1):

[0042] 100 g of porous silicon alloy was added to 100 g of 5 wt% ferric chloride deionized water solution, and reacted at 80° C. for 3 hours, filtered, and vacuum dried at 80° C. for 24 hours to obtain a catalyst-doped silicon alloy material;

[0043] Step S2):

[0044] S21), turning on the target emission source A1, depositing a phosphorus film on the surface of the catalyst-doped silicon alloy material by magnetron sputtering, the thickness of the phosphorus film is 200 nm, and obtaining a phosphorus-doped silicon alloy composite material, wherein the magnetron sputtering method is set according to the following parameters:

[0045] Ammonium phosphate was used as the target emission source A1; the sputtering atmosphere was argon, the sputtering pressure was 5 Pa, the sputtering current was 150 mA, the sputtering voltage was 200 V, the sputtering temperature was 180 ° C, and the sputtering time was 8 minutes;

[0046] S22), stop the target emission source A1, start the target emission source A2, and deposit amorphous carbon on the surface of the phosphorus-doped silicon alloy composite material to obtain an amorphous carbon and phosphorus double-layer coated silicon alloy composite material; wherein the magnetron sputtering method is set according to the following parameters:

[0047] Asphalt was used as the target emission source A2; the sputtering atmosphere was argon, the sputtering pressure was 5 Pa, the sputtering current was 150 mA, the sputtering voltage was 200 V, the sputtering temperature was 180° C., and the sputtering time was 6 minutes.

[0048] The present application conducted a SEM (scanning electron microscope) test on the amorphous carbon and phosphorus double-layer coated silicon alloy composite material obtained in Example 1. The test results are as follows: Figure 1 As shown, we pass Figure 1 It can be seen that the amorphous carbon and phosphorus double-layer coated silicon alloy composite material obtained in Example 1 presents a granular structure with uniform size distribution, and its particle size D50 is between 10-20 μm.

[0049] Embodiment 2:

[0050] Prepare porous silicon alloy, the preparation process is as follows:

[0051] 100g of Si / Ag / Al alloy sheet (weight ratio of 70wt% Si, 15wt% Ag, 15wt% Al, sintered at high temperature) was placed in 1000ml of 10wt% sulfuric acid solution, corroded at room temperature of 30°C for 24 hours, filtered, washed with deionized water 10 times, and then vacuum dried at 80°C for 24 hours to obtain a porous silicon alloy material.

[0052] Step S1):

[0053] 100 g of porous silicon alloy was added to 100 g of 1 wt% cobalt chloride solution, and reacted at 60° C. for 6 hours, filtered, and vacuum dried at 80° C. for 24 hours to obtain a catalyst-doped silicon alloy material;

[0054] Step S2):

[0055] S21), turning on the target emission source A1, depositing a phosphorus film on the surface of the catalyst-doped silicon alloy material by magnetron sputtering, the thickness of the phosphorus film is 50 nm, and obtaining a phosphorus-doped silicon alloy composite material, wherein the magnetron sputtering method is set according to the following parameters:

[0056] Diammonium hydrogen phosphate was used as the target emission source A1; the sputtering atmosphere was argon, the sputtering pressure was 1 Pa, the sputtering current was 100 mA, the sputtering voltage was 100 V, the sputtering temperature was 200 ° C, and the sputtering time was 20 minutes;

[0057] S22), stop the target emission source A1, start the target emission source A2, and deposit amorphous carbon on the surface of the phosphorus-doped silicon alloy composite material to obtain an amorphous carbon and phosphorus double-layer coated silicon alloy composite material; wherein the magnetron sputtering method is set according to the following parameters:

[0058] Artificial graphite was used as the target emission source A2; the sputtering atmosphere was argon, the sputtering pressure was 1 Pa, the sputtering current was 100 mA, the sputtering voltage was 100 V, the sputtering temperature was 200° C., and the sputtering time was 15 minutes.

[0059] Embodiment 3:

[0060] Prepare porous silicon alloy, the preparation process is as follows:

[0061] Place 100g of Si / Ag / Al alloy sheet (weight ratio of 90wt% Si, 5wt% Ag, 5wt% Al, sintered at high temperature) in 1000ml of 40wt% sulfuric acid solution, corrode at room temperature of 30°C for 24 hours, filter, wash with deionized water 10 times, and then vacuum dry at 80°C for 24 hours to obtain a porous silicon alloy material.

[0062] Step S1):

[0063] 100 g of porous silicon alloy was added to 100 g of 10 wt% nickel chloride solution, and reacted at 100° C. for 1 hour, filtered, and vacuum dried at 80° C. for 24 hours to obtain a catalyst-doped silicon alloy material;

[0064] Step S2):

[0065] S21), turning on the target emission source A1, depositing a phosphorus film on the surface of the catalyst-doped silicon alloy material by magnetron sputtering, the thickness of the phosphorus film is 500 nm, and obtaining a phosphorus-doped silicon alloy composite material, wherein the magnetron sputtering method is set according to the following parameters:

[0066] Silicon phosphate was used as the target emission source A1; the sputtering atmosphere was argon, the sputtering pressure was 10Pa, the sputtering current was 200mA, the sputtering voltage was 300V, the sputtering temperature was 200°C, and the sputtering time was 5 minutes;

[0067] S22), stop the target emission source A1, start the target emission source A2, and deposit amorphous carbon on the surface of the phosphorus-doped silicon alloy composite material to obtain an amorphous carbon and phosphorus double-layer coated silicon alloy composite material; wherein the magnetron sputtering method is set according to the following parameters:

[0068] Hard carbon was used as the target emission source A2; the sputtering atmosphere was argon, the sputtering pressure was 10 Pa, the sputtering current was 200 mA, the sputtering voltage was 300 V, the sputtering temperature was 200° C., and the sputtering time was 9 minutes.

[0069] Example 4: The rest of the technical solutions of Example 4 are the same as those of Example 1, except that, in Example 4, the Si / Ag / Al alloy sheet is replaced by a Si / Ag alloy sheet (with a weight ratio of 80wt% Si and 20wt% Ag, sintered at high temperature).

[0070] Example 5: The rest of the technical solutions of Example 5 are the same as those of Example 1, except that, in Example 5, the Si / Ag / Al alloy sheet is replaced by a Si / Al alloy sheet (with a weight ratio of 90wt% Si and 10wt% Al, sintered at high temperature).

[0071] Comparative Example 1:

[0072] 100 g of the catalyst-doped silicon alloy material obtained in step S1) of Example 1 was weighed separately, and 5 g of asphalt was added to a ball mill and mixed evenly. Then, the mixture was transferred to a tubular furnace, and methane gas was introduced. The mixture was carbonized at 950° C. for 3 hours to obtain an amorphous carbon-coated silicon alloy composite material.

[0073] Comparative Example 2:

[0074] The rest of the technical solutions of this comparative example 2 are the same as those of Example 1, except that, in this comparative example 2, step S1) is eliminated, and the catalyst-doped silicon alloy material used in step S2) is replaced by a well-known nano-silicon / silicon-oxygen composite material.

[0075] Comparative Example 3: The rest of the technical solutions of this comparative example 3 are the same as those of Example 1, except that, in step S2) of this comparative example 3, chemical vapor deposition is used to achieve double-layer coating of the Si / Ag / Al alloy sheet with phosphorus film and amorphous carbon.

[0076] Comparative Example 4: The rest of the technical solutions of this comparative example 4 are the same as those of Example 1, except that, in this comparative example 4, step S1) is cancelled, and the porous silicon alloy material is directly used as the substrate to proceed to step S2).

[0077] In order to compare and verify the effects of the above embodiments and comparative examples, the present application uses the silicon alloy composite materials obtained in the above embodiments 1-5 and comparative examples 1-4 as the active material raw material of the negative electrode material of the lithium ion battery, and assembles them by the following method to obtain 9 button batteries, which are respectively recorded as A1, A2, A3, A4, A5, B1, B2, B3, and B4:

[0078] A binder, a conductive agent and a solvent are added to the silicon alloy composite materials corresponding to Examples 1-5 and Comparative Examples 1-4, and the mixture is stirred to make a slurry, which is then coated on a copper foil, and dried and rolled to obtain a negative electrode sheet, wherein the binder used is LA136D binder, the conductive agent is conductive carbon black (SP), the solvent is double distilled water, and the silicon alloy composite material and the negative electrode material are: SP: LA136D: double distilled water = 95g: 1g: 4g: 220ml; a metal lithium sheet is used as the counter electrode, a polyethylene (PE), polypropylene (PP) or polyethylene propylene (PEP) composite membrane is used as the diaphragm, and LiPF6 / EC+DEC (1:1) is used as the electrolyte; and button batteries are assembled in an argon-filled glove box.

[0079] In the present application, the button batteries A1, A2, A3, A4, A5, B1, B2, B3, and B4 prepared in accordance with the above embodiments 1-5 and comparative examples 1-4 were respectively subjected to electrochemical performance tests, wherein the electrochemical performance tests were conducted on a 5V / 10mA battery tester of Wuhan Landian Xinwei, wherein the charge and discharge conditions adopted during the test were: a charge and discharge voltage range of 0.005V-2.0V, a charge and discharge rate of 0.1C, and a test cycle performance (0.1C / 0.1C, 100 times), and the full charge expansion of the corresponding negative electrode sheet was also tested, wherein the test process of the full charge expansion was as follows:

[0080] The thickness D1 of the negative electrode plate is tested in advance, and then the corresponding button battery is fully charged to 100% SOC, and then the full-charge thickness D2 of the corresponding negative electrode plate is dissected, and then the full-charge expansion rate is calculated = (D2-D1) / D1*100%.

[0081] The specific surface areas of the powder materials corresponding to Examples 1-5 and Comparative Examples 1-4 were tested according to the method of national standard GB / T 38823-2020 "Silicon Carbon". The OI values ​​of the powder materials corresponding to Examples 1-5 and Comparative Examples 1-4 were tested by XRD equipment. The electrical conductivity of the powder materials corresponding to Examples 1-5 and Comparative Examples 1-4 was tested by a four-probe tester.

[0082] The test results are shown in Table 1 below:

[0083] Table 1

[0084]

[0085] As can be seen from Table 1 above, the discharge capacity and efficiency of the button battery prepared by the double-layer amorphous carbon and phosphorus coated silicon alloy composite material obtained in Examples 1-5 are significantly higher than those in Comparative Examples 1-4. Therefore, it can be confirmed that the negative electrode material provided in this embodiment can make the battery have good discharge capacity, initial efficiency and conductivity. The reason may be that the negative electrode material prepared in Examples 1-5 is doped with phosphorus with electronic conductivity, which reduces impedance, improves the structural stability of the material and reduces the OI value of the material; at the same time, the amorphous carbon coated on the surface of the silicon alloy material can further restrain the expansion of the silicon alloy material during the charge and discharge process.

[0086] In order to further compare and verify the effects of the above embodiments and comparative examples, the present application also uses the silicon-based composite materials obtained in the above embodiments 1-5 and comparative examples 1-4 as active material raw materials for negative electrode materials of lithium ion batteries, and assembles them by the following method to obtain 9 soft-pack batteries with a specification of 5Ah. According to the order of embodiments 1-5 and comparative examples 1-4, the corresponding soft-pack batteries prepared are marked as C1, C2, C3, C4, C5 and D1, D2, D3, D4 respectively:

[0087] The amorphous carbon and phosphorus double-layer coated silicon alloy composite materials obtained in Examples 1-5 and Comparative Examples 1-4 and doped with 90% artificial graphite were used as negative electrode materials, the ternary material NCM111 was used as positive electrode material, LiPF6 / EC+DEC (volume ratio 1:1) was used as electrolyte, and Celgard 2400 membrane was used as separator to prepare 5Ah soft-pack batteries C1, C2, C3, C4, C5, D1, D2, D3, D4 and their corresponding negative electrode sheets, and the full-charge rebound of the negative electrode sheets and the cycle performance of the soft-pack batteries were tested.

[0088] Among them, the test method for full power rebound is as follows:

[0089] The corresponding soft-pack battery was charged to 4.2V, and then the thickness of the fully charged negative electrode plate was tested with a micrometer and compared with the thickness of the plate after rolling, and the full-charge rebound of the plate was calculated. The test results are detailed in Table 2 below.

[0090] Among them, the test method of the cycle test is as follows:

[0091] The voltage range is 2.5-4.2V, the charge and discharge is 1C / 1C, and the cycle is 500 times. The test results are shown in Table 2 below.

[0092] Among them, the test method of the rate test is as follows:

[0093] Each soft-pack battery was fully charged at a rate of 2C, and the ratio of its constant current charging capacity to the constant current and constant voltage charging capacity was tested. The test results are shown in Table 2 below.

[0094] Table 2

[0095]

[0096] It can be seen from Table 2 above that the capacity and capacity retention rate of the soft-pack batteries prepared using the negative electrode materials obtained in Examples 1-5 after multiple cycles are higher than those in Comparative Examples 1-4. The reason may be that: the silicon alloy negative electrode material provided in this embodiment is doped with phosphorus, which significantly improves the structural stability of the material. At the same time, the material obtained by magnetron sputtering has a stable structure and strong bonding force, which improves the cycle performance. In addition, the material of the embodiment of the present application has lower expansion and impedance, which further improves the cycle performance and constant current ratio of the battery to which it is applied.

[0097] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0098] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a double-clad silicon alloy composite material, It is characterized in that The steps are as follows: S1), placing the porous silicon alloy in a 1-10wt% catalyst solution, reacting at a temperature of 60-100°C for at least 1 hour, filtering and drying to obtain a catalyst-doped silicon alloy material; The preparation method of the porous silicon alloy in step S1) comprises: placing the Si / Ag / Al alloy in a 10-40wt% acid solution for corrosion for at least 15 hours, filtering, washing and drying to obtain the porous silicon alloy; the catalyst in step S1 is selected from one of ferric chloride, cobalt chloride, nickel chloride, cobalt sulfate, cobalt sulfate, nickel sulfate or a mixture of any of them; S2), using the catalyst-doped silicon alloy material obtained in step S1) as a matrix, a phosphite compound as a target emission source A1, and a carbon source as a target emission source A2, to prepare an amorphous carbon and phosphorus double-layer coated silicon alloy composite material by magnetron sputtering; The step S2) includes the following steps: S21), turning on the target emission source A1, and depositing a phosphorus film on the surface of the catalyst-doped silicon alloy material by magnetron sputtering, wherein the thickness of the phosphorus film is 50-500 nm, to obtain a phosphorus-doped silicon alloy composite material; S22), stop the target emission source A1, start the target emission source A2, and deposit amorphous carbon on the surface of the phosphorus-doped silicon alloy composite material to obtain the amorphous carbon and phosphorus double-layer coated silicon alloy composite material.

2. The method for preparing the double-coated silicon alloy composite material according to claim 1, It is characterized in that The Si / Ag / Al alloy includes 60-90 wt % of Si atoms, 5-15 wt % of Ag atoms, and 5-15 wt % of Al atoms.

3. The method for preparing the double-clad silicon alloy composite material according to claim 1, It is characterized in that In the magnetron sputtering method of step S2), the sputtering atmosphere used is argon, and / or the sputtering gas pressure is 1-10 Pa, and / or the sputtering current is 100-200 mA, and / or the sputtering voltage is 100-300 V, and / or the sputtering temperature is 150-200° C., and / or the sputtering time is 5-20 minutes.

4. The method for preparing the double-clad silicon alloy composite material according to claim 1, It is characterized in that In the step S2), the phosphate compound is selected from one of ammonium phosphate, diammonium hydrogen phosphate, silicon phosphate, calcium phosphate, magnesium phosphate, basic copper phosphate, diammonium hydrogen phosphate, and nickel phosphate, or a mixture of any of them.

5. The method for preparing the double-clad silicon alloy composite material according to claim 1, It is characterized in that In the step S2), the carbon source is selected from one of asphalt, artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon, or a mixture of any of them.

6. A double-clad silicon alloy composite material, It is characterized in that The double-clad silicon alloy composite material is prepared by the preparation method according to any one of claims 1 to 5.

7. An application of the double-clad silicon alloy composite material according to claim 6, It is characterized in that The double-coated silicon alloy composite material is used as an active material raw material for preparing battery pole pieces.